PENGARUH PARTISIPASI MASYARAKAT TERHADAP PELAKSANAAN PEMBANGUNAN INFRASTRUKTUR DI DESA KANONANG DUA KECAMATAN KAWANGKOAN BARAT - SONDAKH, CHRISTIAN DEVID BILLI (JURNAL ADMINISTRASI PUBLIK, 2018)
Abstract: This research aims to know and analyze the extent of the influence of Community Participation onthe Implementation of Infrastructure Development in Kanonang Village two Subdistricts of West kawangkoan.The method that writer use in this research is associative research method based on positivism philosophy, usedby researcher on population or certain sample. Sampling technique used is accindendal sampling techniquefrom research in Kanonang Village two Subdistricts of West Kawangkoan as many as 71 people. Data analysistechniques used are simple regression analysis and simple correlation analysis. Based on the analysis ofcorrelation coefficient (r) = 0,831 which means the correlation of both variables are positive and significant.Based on simple regression analysis obtained value Y = 16,266 + 0,692 which means the relationship betweenthe two variables is positive. While from determination coefficient test obtained R square equal to 0,69 or 69%.With these results can be explained that the contribution of community participation on the implementation ofinfrastructure development by 69% while the rest is the contribution of other factors. Based on the results ofsignificance test obtained F arithmetic = 153,462 with F table of 3,98 at a significance level of 0,05. From thedata obtained F count is greater than F table where F arithmetic 153, 462 > 3,98. Then Ho is rejected and Haaccepted. This means that there is influence between the variables of community participation on theimplementation of infrastructure development variables in Kanonang Village two Subdistricts of Westkawangkoan.Keywords: Community Participation, Implementation of Infrastructure Development